Direct Involvement of Cranial Nerve V at Diagnosis in Patients With Diffuse Intrinsic Pontine Glioma: A Potential Magnetic Resonance Predictor of Short-Term Survival - Colafati, Giovanna Stefania; Voicu, Ioan Paul; Carducci, Chiara; Caulo, Massimo; Vinci, Maria; Diomedi-Camassei, Francesca; Merli, Pietro; Carai, Andrea; Miele, Evelina; Cacchione, Antonella; Tomà, Paolo; Locatelli, Franco; et al. (Frontiers in Oncology, 2019)
Background Diffuse intrinsic pontine glioma (DIPG) has a dismal prognosis. Magnetic resonance imaging (MRI) remains the gold standard for non-invasive DIPG diagnosis. MRI features have been tested as surrogate biomarkers. We investigated the direct involvement of cranial nerve V (CN V) in DIPG at diagnosis and its utility as predictor of poor overall survival. Materials and methods We examined MRI scans of 35 consecutive patients with radiological diagnosis of DIPG. Clinical and radiological data of the patients were collected separately. Direct involvement of CN V was assessed on the diagnostic scans. Patients with an overall survival of less than 24 months were analysed. Overall survival (OS) and time to progression (TTP) were evaluated. Analyzed features were involvement of CN V, sex, age, tumor size, ring enhancement and therapy used as first line of treatment. Correlations between involvement of CN V with disease dissemination and with magnet strength were analyzed. Statistical analysis included Kaplan-Meier curves, log-rank test and Spearman’s Rho. Results Of the 35 patients in our initial cohort, 6 long-term survivors were excluded from survival analysis. Therefore, 29 patients were examined (15 M, 14 F). Four patients in this group presented direct involvement of CN V. Histological data were available in twelve patients. Median OS was 11 months (range 3-23 months). Significant differences in OS were found in direct involvement of CN V (7 months, 95% CI 1.1-12.9 months for involvement of CN V versus 13 months, 95% CI 10.2- 15.7 for lack of involvement of CN V respectively, p<0.049). Significant differences in TTP were found for treatment (4 months, 95% CI 2.6-5.3 months versus 7 months, 95% CI 5.9-8.1 respectively, p<0.027). The other factors did not significantly affect OS (p=NS) and TTP (p=NS), respectively. No significant correlation was found between involvement of CN V and magnet strength or slice thickness (r=-0.201; p=NS). A trend towards positive correlation was found between direct involvement of CN V at diagnosis 31 and dissemination of disease at follow-up (r=0.347; p<0.065), In conclusion, in our cohort direct involvement of CN V correlated with poor prognosis. Based on 34 our data, we suggest